Laparoscopic Surgeries in Pediatric Abdominal Surgical Emergencies - Elena Yu. D’yakonova; Aleksandr Yu. Razumovskii; Abdumanap B. Alkhasov; Alexander A. Baranov; Leyla S. Namazova-Baranova; Aleksandr S. Bekin; Aleksei А. Gusev; Ekaterina A. Romanova (Педиатрическая фармакология, 2018)
The article presents a literature review of pediatric abdominal surgical emergencies in the Russian Federation. The article considers the issues of the development of laparoscopic surgery in pediatrics, the current state of this problem in surgical hospitals, the difficulties associated with transition to minimally invasive surgical interventions, in providing emergency surgical care for children. The possible risks of laparoscopic access and methods for their reduction were analyzed. The advantages of this technique were specified in comparison with open surgical interventions. The reliable economic efficiency of the offered technique was demonstrated. The analysis of the literature sources showed that there was no consensus on laparoscopic treatment for complicated abdominal diseases after previous open repair; and there were also no clear algorithms in clinical practice for complete transition to laparoscopic surgery in children. The analysis revealed very few economic studies on the efficacy of laparoscopic interventions.